Shared and language-specific phonological processing in the human temporal lobe - Ilina Bhaya-Grossman; Matthew K. Leonard; Yizhen Zhang; Laura Gwilliams; Keith Johnson; Junfeng Lu; Edward F. Chang (Nature, 2026)
Abstract All spoken languages are produced by the human vocal tract, which defines the limited set of possible speech sounds. Despite this constraint, however, there exists incredible diversity in the world’s 7,000 spoken languages, each of which is learned through extensive experience hearing speech in language-specific contexts 1 . It remains unknown which elements of speech processing in the brain depend on daily language experience and which do not. In this study, we recorded high-density cortical activity from adult participants with diverse language backgrounds as they listened to speech in their native language and an unfamiliar foreign language. We found that, regardless of language experience, both native and foreign languages elicited similar cortical responses in the superior temporal gyrus (STG), associated with shared acoustic–phonetic processing of foundational speech sound features 2,3 , such as vowels and consonants. However, only during native language listening did we observe enhanced neural encoding in the STG for word boundaries, word frequency and language-specific sound sequence statistics. In a separate cohort of bilingual participants, this encoding of word- and sequence-level information appeared for both familiar languages in the same individual and in the same STG neural populations. These results indicate that experience-dependent language processing involves dynamic integration of both shared acoustic–phonetic and language-specific sequence- and word-level information in the STG.